AXA : creating new CR metrics - Elias, Jaan, (SAGE knowledge. Cases., 2016)
A global leader in the insurance and asset management business, AXA had risen to the top ranks in terms of corporate responsibility (CR) as well. Not content to rest on these laurels, AXA reorganized its CR team into a department with strategy, inspiring a reconsideration of how AXA monitored and measured its CR efforts. The CR group was now looking to create new metrics that tied CR work more closely to AXA's operations and growth.